2017
DOI: 10.1371/journal.pone.0182335
|View full text |Cite
|
Sign up to set email alerts
|

Delays in HIV diagnosis and associated factors among patients presenting with advanced disease at a tertiary care hospital in Beijing, China

Abstract: Delayed diagnosis of HIV infection is associated with advanced immunosuppression and increased risk of onward transmission. Little data exists regarding factors associated with diagnostic delays among patients presenting with advanced HIV disease in China. Medical records of patients with HIV/AIDS hospitalized at a 2000-bed tertiary hospital in Beijing, China between 1997 and 2012 were retrospectively reviewed. Demographic and clinical data of patients newly diagnosed with HIV at the hospital were abstracted. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 19 publications
1
10
1
2
Order By: Relevance
“…Another study from a large tertiary referral hospital in Beijing aimed to quantify the delay in time from the initial presentation to any healthcare settings to the ultimate HIV/AIDS diagnosis and found that the average length of diagnostic delay decreased from 91 days in 1997-2002 to 39 days in 2009-2012. However, the severity of disease at the time of diagnosis remained unchanged over the two time periods, as demonstrated by the fact that over 60% of newly diagnosed patients had CD4 counts below 50 cells/μL regardless of the time periods [33]. Furthermore, these patients presented with non-specific symptoms, and had sought care in various departments before ultimately being diagnosed with HIV/AIDS [34].…”
Section: Late Presenters and Delayed Diagnosismentioning
confidence: 99%
“…Another study from a large tertiary referral hospital in Beijing aimed to quantify the delay in time from the initial presentation to any healthcare settings to the ultimate HIV/AIDS diagnosis and found that the average length of diagnostic delay decreased from 91 days in 1997-2002 to 39 days in 2009-2012. However, the severity of disease at the time of diagnosis remained unchanged over the two time periods, as demonstrated by the fact that over 60% of newly diagnosed patients had CD4 counts below 50 cells/μL regardless of the time periods [33]. Furthermore, these patients presented with non-specific symptoms, and had sought care in various departments before ultimately being diagnosed with HIV/AIDS [34].…”
Section: Late Presenters and Delayed Diagnosismentioning
confidence: 99%
“…(21) Result regarding opportunistic diseases also reveals us looking for a diagnosis based on the appearance of signs and symptoms, which reiterates the suggestion of late diagnosis. (25) Implementation of early diagnosis, proper management and correct coping are essential measures to reduce correlated lethality. (26) Presence of two or more clinical manifestations characterizes the symptomatic phase of the infection, suggesting an advanced stage of the infection.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, individuals diagnosed through PITC had greater odds of late presentation and greater odds of presentation with advanced HIV disease compared to individuals diagnosed through VCT and MHT. Furthermore, in a recently published study by Xie et al .,[ 23 ] among patients attending a tertiary hospital in Beijing between 1997 and 2012, not only was a consistent majority of patients diagnosed very late but also there was evidence of immunocompromised well before HIV testing was finally performed, demonstrating the failure of the PITC strategy to identify cases in a timely manner. These results suggest that PITC in Chinese hospital settings is not targeted for maximally efficient identification of new infections.…”
Section: Discussionmentioning
confidence: 99%
“…Despite dramatic scale-up of a range of testing services, including voluntary counseling and testing (VCT, an opt-in approach), provider-initiated testing and counseling (PITC, an opt-out approach), and mandatory HIV testing (MHT) in detoxification settings (e.g., detention centers and reeducation-through-labor camps),[ 19 20 ] China continues to struggle with the challenge of late presentation to human immunodeficiency virus (HIV) care. [ 21 22 23 ] However, the length of delays in diagnosis has not yet been thoroughly studied in the China setting. Therefore, the primary aim of this study was to test the hypothesis that the duration of infection at the time of diagnosis has decreased over time from 2008 to 2015 in Dehong Prefecture, Yunnan Province, China.…”
Section: Introductionmentioning
confidence: 99%